2019
DOI: 10.1002/etc.4445
|View full text |Cite
|
Sign up to set email alerts
|

SSDs Revisited: Part I—A Framework for Sample Size Guidance on Species Sensitivity Distribution Analysis

Abstract: We propose a framework on sample size for species sensitivity distribution (SSD) analyses, with perspectives on Bayesian, frequentist, and even nonparametric approaches to estimation. The intent of a statistical sample size analysis is to ensure that the implementation of a statistical model will satisfy a minimum performance standard when relevant conditions are met. It requires that a statistical model be fully specified and that the means of measuring its performance as a function of sample size be detailed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…The USEPA uses an interspecies toxicity correlation estimation program to indirectly assess threatened and endangered species based on the hypothesis that taxonomically related species (e.g., congenerics) possess similar sensitivities to chemicals (Willming et al 2016). It is abundantly clear from the analyses and approaches described in the present study and in Part I, the companion study (Carr and Belanger 2019) that the need for a consensus and robust guidance on SSD development, application, and interpretation remains significant for chemical safety assessment globally (as per Belanger et al 2017). We add to the existing toolkits for assessing SSD quality, which was identified as a need by the European Centre for Ecotoxicology and Toxicology of Chemicals (2104).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The USEPA uses an interspecies toxicity correlation estimation program to indirectly assess threatened and endangered species based on the hypothesis that taxonomically related species (e.g., congenerics) possess similar sensitivities to chemicals (Willming et al 2016). It is abundantly clear from the analyses and approaches described in the present study and in Part I, the companion study (Carr and Belanger 2019) that the need for a consensus and robust guidance on SSD development, application, and interpretation remains significant for chemical safety assessment globally (as per Belanger et al 2017). We add to the existing toolkits for assessing SSD quality, which was identified as a need by the European Centre for Ecotoxicology and Toxicology of Chemicals (2104).…”
Section: Discussionmentioning
confidence: 97%
“…In the case of SSDs based on chronic data commonly applied to wastewater contaminants and high production volume chemicals with wide‐dispersive use, the application factor need not consider acute‐to‐chronic extrapolation as long as the input data are derived from a true chronic perspective (long‐term exposure, sensitive endpoints of ecological and regulatory significance, statistically robust). Carr and Belanger () have demonstrated that sample size is a relevant factor and that when input data are sufficient in number, the HC5 output is robust, especially at n > 13. Intraspecies variability can be controlled through sound documentation and application of testing principles, as identified by Harris et al ().…”
Section: Discussionmentioning
confidence: 99%
“…12 An SSD is a probabilistic extrapolation (distribution) of certain toxicological endpoints for a set of different species (species sensitivities, such as LC 50 values). 13 The SSD approach has been used to characterize environmental risk for aquatic ecosystems. 14,15 Several soil-dwelling beneficial organisms have been identified in fruit orchards.…”
Section: Species Sensitivity Distribution In Risk Assessmentmentioning
confidence: 99%
“…SSDs were constructed using the SSD in R package developed by P&G (Cincinnati, USA) and discussed in Carr and Belanger [46] and Belanger and Carr [47]. SSDs were fit to a log-logistic model following normalization to C10 to C14 individual CLs and an average environmental exposure CL of C11.5.…”
Section: Ssds and Mesocosmmentioning
confidence: 99%
“…The SSD HC5 for each homologue was calculated for each individual LAS homologue using methods described in Belanger and Carr [46]. In addition, LAS QSARs were used to normalize the mesocosm NOEC for each LAS homologue based on the mesocosm study using the QSAR that provided the most sensitive result.…”
Section: Evaluation Of the Risk From Las In Japan Surface Waters: Tu mentioning
confidence: 99%